Drugs behind the veil of Islam: a view of Saudi youth - Jiang, Guoping (Crime, law and social change, 2021)
Insufficient research exists on drug trafficking and abuse in Saudi Arabia. This paper aims to uncover how drugs are trafficked to Saudi Arabia, what factors contribute to an ever-growing drug use in the Kingdom, and what the life of illegal drug use looks like in such an Islamic environment. Documentary methods and in-depth interviews were adopted to associate drug problems with social environments. It is discovered that drug trafficking is correlated to economic disparity among regions and social strata in the Kingdom, methods of drug purchase differ regionally, and drug use is an unintended consequence of social changes. The study concludes that drug offenses, countering traditional associations of Saudi society, creates a double life in the Kingdom.